2010
DOI: 10.1371/journal.pone.0008936
|View full text |Cite
|
Sign up to set email alerts
|

Defective Secretion of Islet Hormones in Chromogranin-B Deficient Mice

Abstract: Granins are major constituents of dense-core secretory granules in neuroendocrine cells, but their function is still a matter of debate. Work in cell lines has suggested that the most abundant and ubiquitously expressed granins, chromogranin A and B (CgA and CgB), are involved in granulogenesis and protein sorting. Here we report the generation and characterization of mice lacking chromogranin B (CgB-ko), which were viable and fertile. Unlike neuroendocrine tissues, pancreatic islets of these animals lacked co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 53 publications
5
57
0
1
Order By: Relevance
“…Under these conditions, it is possible that insulin plays a role as paracrine regulator of somatostatin release, since, at least in our hands, the two hormones were released at similar glucose concentrations. This is consistent with a previous study using human islets [10], but contrasts with other reports of enhanced delta cell sensitivity to glucose compared with beta cells, where glucose concentrations as low as 2 to 3 mmol/l initiated significant increases in somatostatin secretion from mouse islets [12,38,39]. Because of these reports, we routinely used a very low concentration of glucose (1 mmol/l) to assess basal, unstimulated levels of somatostatin secretion, but were consistently unable to detect any significant increases in somatostatin secretion from mouse islets at 5 mmol/l glucose, whereas we did observe (non-significant) increases in insulin and somatostatin release at 7 and 10 mmol/l glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Under these conditions, it is possible that insulin plays a role as paracrine regulator of somatostatin release, since, at least in our hands, the two hormones were released at similar glucose concentrations. This is consistent with a previous study using human islets [10], but contrasts with other reports of enhanced delta cell sensitivity to glucose compared with beta cells, where glucose concentrations as low as 2 to 3 mmol/l initiated significant increases in somatostatin secretion from mouse islets [12,38,39]. Because of these reports, we routinely used a very low concentration of glucose (1 mmol/l) to assess basal, unstimulated levels of somatostatin secretion, but were consistently unable to detect any significant increases in somatostatin secretion from mouse islets at 5 mmol/l glucose, whereas we did observe (non-significant) increases in insulin and somatostatin release at 7 and 10 mmol/l glucose.…”
Section: Discussionsupporting
confidence: 91%
“…These mice developed a phenotype of hypertension ) and intolerance to glucose (Obermuller et al 2010). In contrast to the CgA-KO mouse, immuno-histochemistry and western blotting confirmed the absence of CgB and the overexpression of CgA (Fig.…”
Section: Catecholamine Exocytosis From Cgb-ko Chromaffin Cellsmentioning
confidence: 82%
“…Further support came from complementary experiments, which showed that over-expression of chromogranin A in non-secretory cells resulted in the formation of secretory vesicles-like structures [38]. On the other hand, deletion of the chromogranin A gene did not affect the synthesis of proteins targeted to the secretory granules or their biogenesis [41] and, in other cell types, such as pancreatic β-cells, insulin vesicle biogenesis was completely independent from both chromogranin A and B [42, 43]. Moreover, chromogranin A ablation resulted in the compensatory expression of other granins.…”
Section: Regulated Exocytosismentioning
confidence: 99%